1995
DOI: 10.1108/09513579510100707
|View full text |Cite
|
Sign up to set email alerts
|

Auditor professional performance and the mentor relationship within the public accounting firm

Abstract: Formal mentoring programmes have developed in public accounting firms in order to gain career development and organizational advantages and, although there is substantial literature concerning problems with formal mentoring programmes, there are few studies which actually have compared the mentoring process at firms with a programme with those using an informal process. Compares mentoring activities at each level in two accounting firms, one using a formal mentoring programme and the other an informal approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Formal mentoring schemes have become increasingly more common (Leibowitz, Farren & Kaye, 1986). Siegel et al (1995) found that, in accounting firms, there are no differences in the influence on career development between formal mentoring and informal mentoring, although they did find significant differences in personal development. Additionally, it has been suggested (Noe, 1988;Chao et al, 1992) that more favourable outcomes come from protégé-driven mentoring arrangements and that protégés often seek the…”
Section: Informal or Formal Mentoringmentioning
confidence: 99%
“…Formal mentoring schemes have become increasingly more common (Leibowitz, Farren & Kaye, 1986). Siegel et al (1995) found that, in accounting firms, there are no differences in the influence on career development between formal mentoring and informal mentoring, although they did find significant differences in personal development. Additionally, it has been suggested (Noe, 1988;Chao et al, 1992) that more favourable outcomes come from protégé-driven mentoring arrangements and that protégés often seek the…”
Section: Informal or Formal Mentoringmentioning
confidence: 99%
“…Mentoring is an organizational instrument that has intention and goal, and therefore presumably improves the individual's possibility to handle the career path through the organization. It has been shown that mentoring has a positive impact on an individual's career (e.g., Arnold & Johnson, 1997; Kram, 1985; Siegel et al ., 1995). The mentor can create access both to resources and networks in the organization (Seibert et al ., 2001), and warn about pitfalls in the organization or the career.…”
Section: The Gendered Career Rein In the Auditor's Certification Processmentioning
confidence: 99%
“…Additionally, a mentor at an auditing firm can educate the assistant in the noble art of auditing. Together with different co‐authors, Siegel has shown that mentoring increases audit efficiency and decreases perceived stress and cultural shocks that may occur during auditing of international firms (Siegel & Reinstein, 2001; Siegel et al ., 1995, 1999, 2001). A formal mentoring programme especially appears to have this effect.…”
Section: The Gendered Career Rein In the Auditor's Certification Processmentioning
confidence: 99%
“…According to organisational socialisation research, an employee's adjustment to the organisation is directly affected by the methods of socialisation adopted by the organisation (Anderson‐Gough et al ., 1998; Fogarty and Ravenscroft, 2000). At entry, a new recruit is generally confronted with an unfamiliar and ambiguous organisational context, and will attempt to make sense of that context (Siegel et al ., 1995). Such recruits, in turn, are seen to look to individuals in senior positions, and/or to company norms and procedures as displayed by the other staff for guidance on what is acceptable or unacceptable behaviour.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Such recruits, in turn, are seen to look to individuals in senior positions, and/or to company norms and procedures as displayed by the other staff for guidance on what is acceptable or unacceptable behaviour. Mentoring is regarded as a sponsorship system in which a senior staff member will take a personal interest in and perform advisory and guidance functions to develop their protégés’ careers (Siegel et al ., 1995). Early studies by Kram (1983), Noe (1988) and Scandura and Viator (1994), indicate that mentors might provide a career‐related mentoring function at a more social level.…”
Section: Hypotheses Developmentmentioning
confidence: 99%